Cultural identity and the purposes of God: a biblical theology of ethnicity, nationality, and race - Bryan, Steven M. (Crossway, 2022)
Steven Bryan presents a biblical framework for thinking about various ideologies of cultural identity and cultivating diversity as the positive good that God intended.